Multiannual top-down estimate of HFC-23 emissions in East Asia - Fang, X.; Stohl, A.; Yokouchi, Y.; Kim, J.; S Li; T. Saito; S. Park; J. Hu (Environ Sci TechnolEnviron Sci Technol, 2015)
Trifluoromethane (CHF3, HFC-23), with a 100-year global warming potential (GWP) of 12400, is regulated under the Kyoto Protocol. HFC-23 emissions in East Asia, especially in China, are currently thought to represent the majority of global HFC-23 emissions. This study provides both a bottom-up emission inventory and the multiannual top-down estimate of HFC-23 emissions in East Asia during 2007-2012. The new bottom-up inventory yields improved simulated HFC-23 mixing ratios compared to previous bottom-up inventories. The top-down estimate uses inverse modeling to further improve the model-measurement agreement. Results show that China contributed 94-98% of all HFC-23 emissions in East Asia. Annual a posteriori emissions from China were around 6.3 Gg/yr during the period 2007-2010 after which they increased to 7.1 +/- 0.7 Gg/yr in 2011 and 8.8 +/- 0.8 Gg/yr in 2012. For the first time, this study also provides a top-down estimate of HFC-23/HCFC-22 (chlorodifluoromethane, CHClF2) coproduction ratios in non-CDM (Clean Development Mechanism) HCFC-22 production plants as well as in all HCFC-22 production plants in China.
Keywords: Air Pollutants/*analysis; China; Chlorofluorocarbons, Methane/*analysis; Far East; Global Warming